Diagnosis of Immune Thrombocytopenia with a Chief Complaint of Ill-Fitting Denture: A Case Report - Majid Sanatkhani; Zahra Delavarian; Atessa Pakfetrat; Negin Samiee (Mashhad University of Medical Sciences, 2019)
Introduction: Immune Thrombocytopenia (ITP)is characterized by its autoimmune response to platelet degradation. The manifestations in symptomatic patients include bruising and multiple bleeding caused by a decrease in the number of platelets.  Case report: This case report presented a 75-year-old male patient referred to the Department of Oral and Maxillofacial Diseases affiliated to the School of Dentistry, Mashhad University of Medical Science, Mashhad, Iran, with a chief complaint of ill-fitting dentures in the last 10 days. The oral examination confirmed the presence of purpura and ecchymosis on the palate and two hemorrhagic bullae on the right mandibular ridge. Moreover, bruisesand red macules were observed on his legs during the clinical examination. The patient was prescribed to receive an emergency blood test. He was referred to the hospital after the diagnosis of severe thrombocytopenia and the possible diagnosis of ITP or leukemia. Eventually, the diagnosis of ITP was confirmed, and he was subjected to a high dose corticosteroid therapy and chemotherapy with intravenous rituximab. The patient recovered fully after two follow-ups within one year.  Conclusion: It is of utmost importance to do oral examinations in patients who have ill-fitting and old dentures since theseelderly patients can be more prone to different blood dyscrasias. In some cases, oral changes are among the first manifestations of systemic diseases.  Early diagnosis has a dramatic effect on the survival rate of the patients along with early referral for the treatment.